One-step structure-directing approach to Ce3+-doped CaS luminescent micro-nanocrystals. Issue 45 (23rd October 2015) - Qiu, Zhongxian; Lian, Hongzhou; Luo, Tingting; Fan, Jian; Cai, Xuechao; Cheng, Ziyong; Shang, Mengmeng; Lian, Shixun; Lin, Jun
Abstract : A non-aqueous, low-temperature, surfactant–ligand co-assisted solvothermal technique is proposed for the synthesis of shape- and size-controlled CaS:Ce 3+ luminescent micro-nanocrystals. Abstract : A one-step surfactant–ligand co-assisted solvothermal technique was proposed for the preparation of CaS-based luminescent materials with ethylenediamine as solvent, and acetylacetone, 1-dodecanethiol and polyvinylpyrrolidone as capping agents. The morphologies of the obtained particles can be adjusted from an octahedron to a hexagonal prism or a cube by changing the solvent volume ratios of ethylenediamine and different capping agent(s), and the mean sizes of the crystals can be changed in a relatively wide range from tens of nanometers to a few micrometers. The growth process and dynamic mechanism were discussed. A series of CaS: x Ce 3+ nanocrystals were prepared and a small red shift of emission positions was observed from green to yellowish-green with increasing Ce 3+ concentration.